2001
DOI: 10.1002/jmv.2028
|View full text |Cite
|
Sign up to set email alerts
|

Genotype may correlate with liver carcinogenesis and tumor characteristics in cirrhotic patients infected with hepatitis B virus subtype adw

Abstract: To identify the influence of hepatitis B virus (HBV) genotype on development of hepatocellular carcinoma (HCC) and clinical outcome in chronic HBV infection, 26 consecutive cirrhotic patients infected with HBV subtype adw were investigated prospectively. HBV serology was undertaken using subtype-specific antibodies against hepatitis B surface antigens. The HBV genotype was determined by sequencing directly the polymerase chain reaction products of the HBV S gene. When HCC occurred, patients underwent transcath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 40 publications
1
86
1
2
Order By: Relevance
“…For example, HBV genotypes C and D are more difficult to treat than genotypes A and B [113,114]. There is also some evidence suggesting an increased pathogenicity of genotype C over B, with a greater likelihood of developing HCC [115,116].…”
Section: Hbv Resistance Testingmentioning
confidence: 99%
“…For example, HBV genotypes C and D are more difficult to treat than genotypes A and B [113,114]. There is also some evidence suggesting an increased pathogenicity of genotype C over B, with a greater likelihood of developing HCC [115,116].…”
Section: Hbv Resistance Testingmentioning
confidence: 99%
“…Some studies have recently suggested that the HBV genotype is correlated with the clinical features of HBV infection and with the response to antiviral treatments. In fact, with regard to genotypes B and C, which are prevalent in Asia, genotype C has been shown to be more frequently found in severe liver disease and in hepatocellular carcinoma and it presents a lower response rate to interferon alfa therapy, while genotype B is associated with faster HbeAg/antiHBe seroconversion (4,5,6,8,18,20) . During treatment with lamivudine, YMDD variants seem to appear faster in genotype A patients than genotype D but appear earlier in genotype D (19) .…”
Section: Introductionmentioning
confidence: 99%
“…HBV genotype C is associated with more severe histological liver damage and low-grade responses to interferon therapy [22] . Moreover, patients with genotype C show poor responses to embolization therapy and may die from hepatic failure because of rapid hepatocellular carcinoma (HCC) progression [23] . Another study has reported that HBV genotype C has more rapid selection of lamivudine resistance than genotype B [17] .Therefore, further studies of HBV YMDD mutants with genotype C are of great significance.…”
Section: Discussionmentioning
confidence: 99%